Kinetics of Oxidation of 2-Methoxyethanol by Quinolinium Dichromate - Elizabeth Phebe, D.; Wilfred Sugumar, R. (Asian Journal of Chemistry, 2010)
Kinetics of oxidation of 2-methoxyethanol by quinolinium dichromate (QDC) has been studied in aqueous acetic acid medium. The title reaction is first order in [oxidant] and [substrate], and second order in [H+]. Activation parameters have been evaluated. A suitable mechanism has been proposed on the basis of the results of the kinetic studies.